Pre-Paid Phone Distribution: A Tool for Improving Healthcare Engagement for People with Substance Use Disorder. (21st March 2023) - Peterkin, Alyssa F.; Jawa, Raagini; Menezes, Kalil; You, Jacqueline; Cabral, Howard; Ruiz-Mercado, Glorimar; Park, Tae Woo; Kehoe, Jessica; Taylor, Jessica L.; Weinstein, Zoe M.
Abstract: Background: The COVID-19 pandemic drove significant disruptions in access to substance use disorder (SUD) treatment and harm reduction services. Healthcare delivery via telemedicine has increasingly become the norm, rendering access to a phone essential for engagement in care. Methods: Adult patients with SUD who lacked phones ( n  = 181) received a free, pre-paid phone during encounters with inpatient and outpatient SUD programs. We evaluated changes in healthcare engagement including completed in-person and telemedicine outpatient visits and telephone encounters 30 days before and after phone receipt. We used descriptive statistics, where appropriate, and paired t-tests to assess the change in healthcare engagement measures. Results: Patients were predominantly male (64%) and white (62%) with high rates of homelessness (81%) and opioid use disorder (89%). When comparing 30 days before to 30 days after phone receipt, there was a significant increased change in number of telemedicine visits by 0.3 (95% CL [0.1, 0.4], p  < 0.001) and telephone encounters by 0.2 (95% CL [0.1, 0.3], p  = 0.004). There was no statistically significant change in in-person outpatient visits observed. Conclusions: Pre-paid phone distribution to patients with SUD was associated with an increased healthcare engagement including telemedicine visits and encounters.